TECHNOLOGY ADOPTION, TECHNOLOGY MANAGEMENT AND ITS IMPACT ON OPERATIONAIL PERFORMANCE: A CASE FROM INDONESIA - LENA ELLITAN (Jurnal Bisnis dan Akuntansi, 2002)
This paper is base in a field investigation via face to face interviews with top management, that was done in East Java involved medium and large manufacturing companies. They operate in the tobacco, plasctic, pulp, furniture, textile, cable and plywood business area. This research is an exploratory one that was conducted to examine the extent of technology adoption and its management in medium and large manufacturing companies in Indonesia. This study also investigates the impact of technology adoption on performance of the firms. The analysis of this study has shown that there are many internal and external drivers influencing technology adoption. In addition, the successful of technology adoption and implementation depend on: (1) management of technology adoption, which includes all of processes before making decision for adopt new technology and how the companies monitor adoption and implementation of technology. (2) strategy to adopt and implement technology as technology sourcing, choosing product and process technology, and which part the companies develop, adopt and implement new technology. (3) development of technology capabilities through introducing new technology, to up grade skills, knowledge and capabilities of worker, improve organization structure and culture, collaboration with supplier and customer, as well as benchmarking. Finally, the issue of cost, people or human resource, and economic situation were some of the problem faced by these organizations that somewhat affect that performance.